Omah Rojolele: Pelestarian Budaya Agraris dan Pemberdayaan Integratif Interkonektif Desa Delanggu Klaten - Gusti, Kinanthi Ing; Jingga, Lintang Antarikza; Prasetiya, Rio Dwi; Hapsari, Annisa Nur; Hafiya, Aqila; Safitri, Diana Lutfia Nur; Darwis, Gusti Putu Astasidi Ahmad; Maghfiroh, Lailil; Permadi, Muhammad Wildan Dimas; Fawwaz, Prabu Lingga Wijaya; Kedaton, ⁠Prameswari Bunga; Ramadhani, Safitri; Adkia, Tauba Zaka; Ramadhan, Della Amanda; Trengginas, Surya; Rustamaji, Muhammad; Indreswari, Rysca (Unri Conference Series: Community Engagement, 2024)
Delanggu Village is well-known for its agricultural success, particularly as a producer of the Rojolele rice variety. Delanggu Village, which preserves historical values in the agricultural sector, has the potential for cultural preservation through various artistic events in the form of a farming cultural celebration called the Mbok Sri Festival. However, the preservation and strengthening of agricultural culture has only been limited to the Mbok Sri Festival, which is held once a year. As a result, the establishment and reinforcement of agrarian culture in Delanggu Village is not ideal. As a result, new value developments are required to maximize the preservation of agrarian culture and time-limited tourist trips to Delanggu Village. Based on these issues, the PPK Ormawa KSP "Principium" Team, as a service team, collaborated with Delanggu Village to develop a solution idea in the form of community service and empowerment through the implementation of Omah Rojolele as an integrated means of agricultural history to increase the community's attractiveness. The service and empowerment method used is Participatory Rural Appraisal (PRA), which emphasizes active community engagement in the establishment of agricultural cultural villages. This dedication and empowerment has resulted in the strengthening of Delanggu Village's cultural management institutions, the establishment of Omah Rojolele and the Omah Rojolele Website, the development of village connections through cultural tourism packages, and an increase in village income generation.